Exploring the challenges facing in sustaining the Malay cultural landscape elements at Pantai Lido waterfront, Johor Bahru, Malaysia - Hussain, Mohd Amirul; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah; Mohd Ariffin, Noor Fazamimah; Ismail, Sumarni; Hamdan, Hishammuddin (Human Resource Management Academic Research Society, 2022)
In recent years, the urbanisation at Pantai Lido has undergone significant change in its Malay cultural landscape elements, thus has led to the decline of its symbolism of place. Most of the planned constructions at Pantai Lido undertake without any consideration to protect and conserve the local cultural landscape elements as part of the development design strategies. This is due to the regeneration or development blueprint at the waterfront area in Malaysia are still lack in emphasis on the importance of cultural landscape as part of its development and design guideline. The objective of the study to exploring the factors faced by the local stakeholders in maintaining the landscape elements of Malay Culture in Pantai Lido. The study was conducted through qualitative research methods to dismantle the implementation gap that still exists in sustaining the cultural landscape elements in Pantai Lido. The findings determined the Malay cultural landscape elements at Pantai Lido is not able to cope with the massive wave of transformation due to tremendous pressures from the development and weaknesses in planning and design blueprint by responsible authorities. At this point, perhaps Pantai Lido needs proper management and references, sympathetic to the people living in the area, rather than facilitating the flow of gigantic development within the Malay cultural landscape core of Pantai Lido. Thus, it is essential to recognise that time change is inevitable; this continued strain on the waterfront requires a set of principles for governance be to develop that will ensure future sustainability.